2017
DOI: 10.4102/jsava.v88.1379
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Rift Valley fever in cattle along the Akagera–Nyabarongo rivers, Rwanda

Abstract: Rift Valley fever (RVF) virus is caused by a zoonotic arbovirus that is endemic to eastern and southern Africa. It has also been reported in West and North Africa, Madagascar and the Arabian Peninsula. The virus is transmitted by mosquitoes, but people can also become infected while handling blood or other body fluids of animals and humans with RVF. In 2007, there was a large outbreak of RVF in Kenya, Tanzania, Sudan and Somalia. Outbreaks were also reported in South Africa in 2008–2011. The epidemiology of RV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(26 reference statements)
2
12
1
Order By: Relevance
“…The odds of RVFv exposure in females was high than that of males. These findings are similar to those reported from a cross-sectional survey conducted in southern Tanzania [ 14 ] but varied from those from a survey conducted in Rwanda [ 18 ] which did not find any differences in exposure levels by sex. No studies have been done to determine how sex influences RVFv exposure in animals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The odds of RVFv exposure in females was high than that of males. These findings are similar to those reported from a cross-sectional survey conducted in southern Tanzania [ 14 ] but varied from those from a survey conducted in Rwanda [ 18 ] which did not find any differences in exposure levels by sex. No studies have been done to determine how sex influences RVFv exposure in animals.…”
Section: Discussionsupporting
confidence: 88%
“…Exposure through inhalation of aerosolised viral particles especially during outbreaks is also thought to contribute to human exposure [ 16 ]. Factors associated with RVFv exposure in livestock include semi-nomadic pastoralism [ 17 ], advanced age and exotic and crossbreeds compared with local breeds [ 18 ]. Those associated with exposure in people are advanced age [ 19 ], history of animal contact [ 20 ] for instance through animal slaughtering [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Buhara and Bubare subcounties are connected by the primary North-South highway between Kabale town and the Rwandan border, a transportation corridor that could have served as a possible source of introduction of RVFV into Kabale district through livestock trade. A serosurvey of livestock conducted in Rwanda showed overall seropositivity of 16.8%, with districts closest to Tanzania showing the highest seropositivity and the 2 districts closest to the Ugandan border having the lowest seropositivity [ 34 ]. In addition, evidence of previous RVFV circulation and infection of livestock from samples collected in 2009 in goats from the Southeastern districts of Ssembabule, Mpigi, Masaka and Mubende shows a total seroprevalence of approx.…”
Section: Discussionmentioning
confidence: 99%
“…10% [ 24 ]. Although the testing methodologies employed for these samples was different than the one employed in our study, evidence of seropositivity in livestock may begin at earliest in 2009, or possibly earlier, and may suggest that RVFV was introduced into this region following outbreaks in neighboring countries and maintained through low level inter-epidemic transmission [ 34 ]. However, because there are no published reports of RVF seropositivity prior to 2009, we cannot be certain there was no widespread circulation of RVFV before that time.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevelance observed for cattle in this studies were higher than those observed in Madagascar 28% (n = 894) in 2009 [52] and 14% (n = 1353) between 2010–2011 [53], Botswana 5.7% (n = 863), in 2010–2011 [54], Rwanda 16.8% (n = 595) between December 2012 and March 2013 [55] and Tanzania 27.7% (n = 756) in 2013 [47]. Studies carried out in the central (Zambezia and Manica) and south (Maputo and Gaza) Mozambique between 1996 and 2013, have shown high seroprevalence of RVF antibodies in cattle (7% – 51.6%), goats (11.6% – 25.1%), and sheep 9.2% – 44.2%) [29–34].…”
Section: Discussionmentioning
confidence: 57%